A Study of the Availability and Demand of Digital Services for the Manifestation of Social and Political Activity by Citizens - E. Karagulyan; M. Batyreva (BRICS Law Journal)
In recent decades, scientists have been discussing ways of involving the population in social and political processes. Terms such as “civic participation,” “civic control,” “participation in the government of the power-poor,” etc. are widely used in scholarly discourse on this subject. The research related to social and political activities is conducted within various thematic areas based on “political participation theory” and “participatory democracy theory,” as well as on “theories of economic and digital inequalities.” According to the vast majority of scientists, increasing digitalization is known to expand the forms of participation and transform the public administration at all levels concerning joint governance and a citizen-centric approach, taking into consideration the opinion and active participation of citizens in the production and execution of policy decisions. This article presents the results of a study that investigated whether modern digital services allow citizens to participate in and influence the social and political processes taking place at various levels of government. In addition, the study demonstrates how modern digital technologies promote the maximum participation of the most socially vulnerable categories of the population, as well as how such factors as the level of digital competence, the level of income of the population, and the level of digitalization of territories limit this participation. In order to assess the modern digital forms and the use of these forms in a citizen’s interaction with the authorities, a survey of 1,200 residents of villages and towns located in the south Tyumen Region was conducted. The ways in which the residents living in the towns and villages of the Tyumen Region were able to express their civic positions were determined and the proportion of citizens using digital technologies was noted. The study also assessed the availability and demand for digital technologies by citizens to express their social and political activities, as well as the primary factors that limit their social and political participation. Moreover, this research showed that age, education, and digital competence and awareness were the main factors influencing a citizen’s propensity to use modern digital technologies for social and political activity. The hypothesis that the demand for digital services by citizens living in remote districts should be higher than that of urban residents was not confirmed. On the contrary, for a wide range of services, the assessments of demand and accessibility are higher among the residents of cities than among the residents of rural municipal districts, with the highest assessments coming from the residents of the regional capital. This fact is associated with a higher level of digital competence among citizens, a higher level of digitalization of the regional capital, as well as a higher level of income, which allows them to more actively master and use all these services. Additionally, this article is addressed to researchers interested in various aspects of social and political participation, as well as to politicians who make decisions regarding the development and implementation of new forms of digital interaction between citizens and the authorities that enable citizens to demonstrate their civic position.